Stress Levels and Quality of Life of Families Caring for People with Mental Disorders: Literature Review - Sumarsih, Tri; Ningsih, Fina Widya; binti Arsat, Norkiah; Dwidiyanti, Meidiana (Global Health Science Group, 2024)
The family is the main support system for individuals suffering from mental disorders to maintain their health. However, this responsibility can cause psychological reactions to the family, some of which are stress on the family and of course will have an impact on the quality of life that the family has. The aim of this study was to identify stress level and the quality of life of families caring for people with mental disorders. The method of the research used the literature study. The analysis material consists of fourteen articles in Indonesian and English, research published within a period of 5 years (2018-2023), research journal whose respondents are mental disorder families, full-text with the Google Scholar database, Science Direct, Pubmed, Researchgate, Garuda, Scopus, Springerlink, ristekbrin.go.id, Accademia Edu, and Proquest using keyword “tingkat stres keluarga ODGJ”, “kualitas hidup keluarga ODGJ”, “keluarga skizofrenia”, “stress level” AND “schizophrenia family”, “quality of life” AND “mental illness family”, “schizophrenia family”, “caregiver schizophrenia”. Article quality assessment using tables critical appraisal duffy’s. The result analysis of 7 articles related to the stress levels of families caring for patients with mental disorders that have been carried out show that there were 3 articles with mild stress levels, 2 articles with heavy stress, and 1 article with normal stress, and 2 articles with no stress. The results analysis of 7 articles of quality of life on families caring patients with mental disorders showed that families experienced high quality of life in 3 articles, moderate in 2 articles, while low quality of life in 2 articles. Based on the 14 article, it can be concluded that families caring patients with mental disorders experienced stress and have problems in quality of life. For further study, it is hoped adding the article more and review related to risk factor or interventions on stress and quality of life among families caring mental disorder’s patients.